2020
DOI: 10.1051/0004-6361/202037958
|View full text |Cite
|
Sign up to set email alerts
|

First observations and magnitude measurement of Starlink’s Darksat

Abstract: Aims. Measure the Sloan g' magnitudes of the SpaceX STARLINK-1130 (Darksat) and 1113 LEO communication satellites and determine the effectiveness of the Darksat darkening treatment at 475.4 nm. Methods. Two observations of the SpaceX STARLINK Darksat LEO communication satellite were conducted on 2020/02/08 and 2020/03/06 using a Sloan r' and g' respectively. While a second satellite, STARLINK-1113 was observed on 2020/03/06 using a Sloan g' filter. The initial observation on 2020/02/08 was a test observation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The images captured by Tregloan-Reed and Horiuchi in figure 10 show streaks from satellites with coating, although darker, are still persistent in astronomical imaging [59]- [62]. The results also show that the 55% reduction of reflectivity [46], [60] varies in different locations. This could be due to many factors such as the distance from the satellite, the angle of the satellite in relation to the sun and different altitudes of the satellites [61].…”
Section: Iv: Low-albedo Coatingmentioning
confidence: 95%
See 1 more Smart Citation
“…The images captured by Tregloan-Reed and Horiuchi in figure 10 show streaks from satellites with coating, although darker, are still persistent in astronomical imaging [59]- [62]. The results also show that the 55% reduction of reflectivity [46], [60] varies in different locations. This could be due to many factors such as the distance from the satellite, the angle of the satellite in relation to the sun and different altitudes of the satellites [61].…”
Section: Iv: Low-albedo Coatingmentioning
confidence: 95%
“…This means that the satellite terminal antennas on the ground may not receive the signals transmitted by LEO satellites, posing a serious barrier to providing low latency, high bandwidth satellite internet promised by such new constellations. Additionally, [60] Table 2: Data from observatories on the satellite brightness magnitude after the application of low-albedo coating [59]- [62] Fig 10: Apparent Brightness's of some objects in the magnitude system [63]. overheating the antenna system creates interference in infrared observations as the satellites will be visible due to their higher temperature.…”
Section: Iv: Low-albedo Coatingmentioning
confidence: 99%
“…Hainaut & Williams (2020) examined the impact on ESO telescopes in the optical and infrared and concluded that the greatest impact from LEO satellites will be on large telescopes using large field of view (tens of arcmin to a few degrees), and relatively long exposure times (order of few seconds to minutes). The photometric model used by Hainaut & Williams (2020) accurately predicts the magnitude of STARLINK-1113 given by Tregloan-Reed et al (2020), when using the same satellite range and elevation. A second study by McDowell (2020) indicates that LEO satellites with an orbital height of ≤ 600 km will have the greatest impact on twilight astronomy and long exposures using wide fields of view.…”
Section: Introductionmentioning
confidence: 94%
“…Ground-based observations of Darksat shows g ≈ 6.1 mag (Tregloan-Reed et al 2020;Tyson et al 2020) when normalised to the local zenith and accounting for the view angle subtended from the point of view of the satellite between the Sun and observer. When compared to STARLINK-1113, the darkening treatment used by Starlink, reduced the reflective brightness of Darksat by ≈ 0.8 mag (Tregloan-Reed et al 2020) a reduction factor of two, while Tyson et al (2020) determined an average reduction in the reflective brightness of Darksat by ≈ 1.0 mag when compared to a group of Starlink satellites. However the observed reduction in reflective brightness does not allow for nonlinear image artefact correction on ultra-wide-field telescopes such as the Charles Simonyi telescope's camera detectors at the Vera C. Rubin Observatory.…”
Section: Introductionmentioning
confidence: 99%
“…The current studies of the impact of LEO satellites on astronomical observations are based either on simulations (McDowell 2020;Hainaut & Williams 2020;Williams et al 2021;Bassa et al 2021;Lawler et al 2021) or targeted follow-up observations (Tregloan-Reed et al 2020Mallama 2021a,b). However, we expect that these impacts should be greatest for wide-field sky surveys, such as the Zwicky Transient Facility (ZTF, Bellm et al 2019b;Graham et al 2019;Masci et al 2019), Asteroid Terrestrial-impact Last Alert System (ATLAS, Tonry 2011), All-Sky Automated Survey for Supernovae (ASAS-SN, Shappee et al 2014), and-in the future-Vera Rubin Observatory's Legacy Survey of Space and Time (LSST, Tyson et al 2020).…”
mentioning
confidence: 99%